The Influence of Rhythmic Gymnasticsactivities on Gross Motor Development (Children Aged 5-6 Years) - Dwi Yoni Martiana (Journal of Art and Creativity in Early Childhood Education, 2025)
Early childhood is an individual who is experiencing a rapid development process, so that children who are still in preschool need gross motoric development of children and have to do it, one of which is by using rhythmic gymnastics. The aims of this study was to determine the role of rhythmic gymnastics in improving gross motor skills in motor development and to determine gross motoric development of children after doing rhythmic exercise in early childhood. The methodology in this study uses a qualitative approach with literature review research methods on reliable sources such as journal articles, books and the like. Obtained the results of facts and data that the application of rhythmic gymnastics in improving gross motor skills of early childhood means that the more varied and innovative activities there are, the more opportunities to improve gross motor skills in children so that they can develop optimally. The implications of the findings of this paper provide an overview of the application of rhythmic gymnastics in improving gross motor skills in early childhood